2015
DOI: 10.1080/10408398.2013.862201
|View full text |Cite
|
Sign up to set email alerts
|

Comparing and Contrasting Three Cultural Food Customs from Nigeria and Analyzing the Nutrient Content of Diets from These Cultures with the Aim of Proffering Nutritional Intervention

Abstract: Nigeria is a multicultural country with a diverse cultural food. Most Nigerians' cultural diet is based on staple food accompanied by stew. In the South West and Eastern region (where Yorubas and Igbos are the dominant ethnic groups), staple foods are yam and cassava by-product (garri, fufu and lafun) with vegetables prepared as stew, often over cooked, thereby losing essential micronutrients. In Northern Nigeria (where the Hausas and Fulanis are the dominant ethnic groups), grains such as sorghum, millet form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…While Philip and Dipeolu (2010) and Abdulai (2016a, 2016b), in particular, identified different organic food attributes preferred by consumers, only Abdulai (2016a, 2016b) modelled preference heterogeneities, focusing on the northern region of the country. Meanwhile, Nigeria is highly diverse in cultural and dietary patterns (Adegboye et al 2016) and heterogeneous in household wealth (World Bank 2016), such that findings from studies focusing on one region of the nation cannot be applied to the economic settings of another region.…”
Section: March 2021mentioning
confidence: 99%
“…While Philip and Dipeolu (2010) and Abdulai (2016a, 2016b), in particular, identified different organic food attributes preferred by consumers, only Abdulai (2016a, 2016b) modelled preference heterogeneities, focusing on the northern region of the country. Meanwhile, Nigeria is highly diverse in cultural and dietary patterns (Adegboye et al 2016) and heterogeneous in household wealth (World Bank 2016), such that findings from studies focusing on one region of the nation cannot be applied to the economic settings of another region.…”
Section: March 2021mentioning
confidence: 99%
“…Nigeria is one of the major countries in the West African region and has a complex and diverse food culture; therefore the results of the present review on Nigeria may be also applicable to other countries in West Africa (11) . The methodology of this review can be applied to other low-and middle-income countries since the diets are often, just like the Nigerian diet, mostly plant-based (for example, due to costs) and lack variety, which might influence protein intake adequacy.…”
Section: Strengthsmentioning
confidence: 98%
“…In Nigeria, low-cost foods rich in good-quality protein are scant (10) , which makes it difficult to meet protein and amino acid requirements. Studies have been conducted on examining the protein and amino acid composition of certain staple foods and Nigerian diets (11)(12)(13) , protein and specific amino acid requirements in individuals (2,5,9,14,15) , as well as dietary protein intake among children (16) , adolescents (17) and women (18) . However, no clear overview of both the adequacy of dietary intake of protein, in terms of quantity, in Nigerian infants, children, adolescents and (pregnant and lactating) women, and the role of the Nigerian diet and specific staple foods in achieving this adequacy exists.…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum also typically contains provitamin A carotenoids, but the association of sorghum intake and vitamin A deficiency is shown to be contradictory. Studies conducted in Africa indicated various types of malnutrition including vitamin A deficiency when sorghum was the principle grains in the diet (5). However, other studies have suggested that the sorghum consumed in Africa and Asia are critical sources of dietary carotenoids that might provide the needed provitamin A (6).…”
Section: Sorghum Contains the Highest Phytochemical Contents Among Cementioning
confidence: 99%